Opinions and experiences of physicians regarding complementary and alternative medicine (CAM). A research report from Poland - Leśniewska, Magdalena; Kozioł, Ilona; Budzyńska, Julia; Kopystecka, Agnieszka; Patryn, Rafał (Journal of Education, Health and Sport, 2022)
Background: The term CAM denotes complementary and alternative medicine. However, CAM is practiced by individuals without academic medical education and formal eligibility for treating people. The extent of interest in CAM is considerable. The WHO global report on traditional and complementary medicine has demonstrated that 87% of all WHO Member States legally recognise individual forms of CAM, and 100 Member States have national policies regarding such practices. In Poland, performing medical activities without appropriate qualifications is prohibited. Material and Methods: Diagnostic survey distributed as Google Forms was used as the basic research method with the research technique of a questionnaire. The questionnaire starting with a metrics part consisted of several questions regarding popularity and tendency of CAM, causes of CAM popularity, approach to those types of practices and patients as well as role of CAM during the pandemic. Sixty-one responses were obtained from physicians of different age, experience and speciality. Results: Ninety-five percent (95%) of doctors believe that alternative medicine can be dangerous; 67.2% think that the phenomenon of alternative medicine should be combated; almost half of the physicians surveyed believe that there is a fundamental contradiction between evidence-based medicine (EBM) and alternative medicine. Furthermore, according to 48% of respondents, physicians in Poland should be able to recommend and combine methods of traditional and alternative medicine. Conclusion: Doctors point to the increasing popularity of CAM among patients in Poland, the consequences of which cannot be determined because there is still a lack of research on the safety of alternative methods. The most frequently cited reasons for interest in CAM suggest that there is a need for a better tailored biomedical approach to individual patient needs.